Revision of the Apprenticeship and Internship Logbooks of Community Health Nursing - Batol Abbasi; Kazem Hosseinzadeh (Zanjan University of Medical Sciences and Health Services, 2018)
Background: Portfolio is one of the most important tools to inclusive education as well as its evaluation. It is a useful tool in the promotion and development of skills such as critical thinking, and can reduce the gap between theory and practice. Object: The aim of this study was to revision on portfolio of community health nursing. Materials and Methods: This is a qualitative study conducted in educational management paradigm in order to revision in portfolio which was used in Qazvin University of Medical Sciences in 2015. After the literature review various methods of data collection were used. All themes and items of the portfolio were structured in five point Likert scale checklist (completely necessary, necessary, neutral, unnecessary, completely unnecessary). Content validity of the checklist was evaluated qualitatively. Then, the lesson curriculum was evaluated by the researchers based on the late curriculum. Results: Regarded to the main curriculum and the point views of experts 77 items were added in to the portfolio. Health education, home care, and communications did not exist in the original portfolio. The final portfolio set in 10 sections and 142 items. Discussion and Conclusion: Items such as health education and communication have been emphasized in new portfolio. Developing and improving these skills may lead to community health improvement.